Phenylpropanoids in species of plants of the Duguetia genus: A review (Research, Society and Development, 2022)
The genus Duguetia encompasses 93 species, 63 of which are distributed in Brazil. However, only ten species had their chemical and biological profiles investigated so far. Although the alkaloids are the class of phytocompounds most studied, the interest in the phenylpropanoids is growing since distinct biological activities have been attributed to these derivatives lately. This review gathered studies describing the phytochemical distribution, methods of extraction, and biological activities of the phenylpropanoid from Duguetia species. It was evidenced that nonpolar solvents were able to provide the highest yield of 2,4,5-trimethoxystyrene, γ-asarone, and asaraldehyde which were mainly located at the ground stem barks. On the other hand, the α-asarone, elimicin, and (E)-methyl-isoeugenol were isolated from the polar extracts or the essential oils from the barks and leaves. The 2,4,5-trimethoxystyrene and asarone derivates were effective as crop protectors. The α- and γ-asarone, 2,4,5-trimethoxycinnamic acid, asaraldehyde, elemicin, and (E)-methyl-isoeugenol demonstrated anti-inflammatory, antidyslipidemic, antinociceptive, antibacterial, antidepressant, anxiolytic, insecticide, and larvicide activities. The Duguetia species can be a potential source of phenylpropanoids, therefore, future studies involving their extraction, identification, and application are still necessary and may culminate in the discovery of new drug candidates or natural agricultural defensives.